Diazotrophic cyanobacteria in planktonic food webs - Suikkanen Sanna; Uusitalo Laura; Lehtinen Sirpa; Lehtiniemi Maiju; Kauppila Pirkko; Mäkinen Katja; Kuosa Harri (Elsevier BV, 2022)
Blooms of cyanobacteria are recurrent phenomena in coastal estuaries. Their maximum abundance coincides with the productive period of zooplankton and pelagic fish. Experimental studies indicate that diazotrophic, i.e. dinitrogen (N2)-fixing cyanobacterial (taxonomic order Nostocales) blooms affect zooplankton, as well as other phytoplankton. We used multidecadal monitoring data from one archipelago station (1992–2013) and ten open sea stations (1979–2013) in the Baltic Sea to explore the potential bottom-up connections between diazotrophic and non-diazotrophic cyanobacteria and phyto- and zooplankton in natural plankton communities. Random forest regression, combined with linear regression analysis showed that the biomass of cyanobacteria (both diazotrophic and non-diazotrophic) was barely connected to any of the phytoplankton and zooplankton variables examined. Instead, physico-chemical variables (salinity, temperature, total phosphorus), as well as spatial and temporal variability seemed to have more significant connections to both phytoplankton and zooplankton variables. Zooplankton variables were also connected to the biomass of phytoplankton groups other than cyanobacteria (such as chrysophytes, cryptophytes and prymnesiophytes), and phytoplankton variables had connections with the biomass of different zooplankton groups, especially copepods. Overall, negative relationships between cyanobacteria and other plankton taxa were scarcer than expected based on previous experimental studies.
​​​​​​​